Effects of 15 mg meloxicam administered before odontectomy on pain, facial edema, trismus, and expressions of TNF following odontectomy of impacted mandibular third molar - Melisa Ruth; Cahya Y. Hasan; Rustamadji Rustamadji; Rahardjo (DiscoverSys Inc., 2020)
Objective:To evaluate the effects of 15 mg meloxicam administered 60 minutes before odontectomy on pain, facial edema, trismus and expressions of TNF-Î± after odontectomy of impacted mandibular third molar.Material and Methods: A total of 24 patients were randomized into treatment groups, each with 12 patients: Group A was administered with 15 mg of meloxicam; and Group B with placebo. Drugs were administered orally 60 minutes prior to surgery. Observation of pain (seen from VAS scores), facial edema (seen from swollen cheeks), trismus (seen from mouth opening) and expressions of TNF-Î± (measured from saliva by ELISA method), performed before odontectomy, H+1 (24 hours after odontectomy) and H+3 (72 hours after odontectomy).Results: Patients who received 15 mg meloxicam 60 minutes before odontectomy showed less postoperative pain (p=0.000), less facial edema (p=0.000) and lower expressions of TNF-Î± (p=0.000). No differences were found in mouth opening between the meloxicam group and placebo group (p=0.522). The higher level of TNF-Î± level will lead to higher level of pain, greater facial edema and causes smaller mouth opening.Conclusion: Oral administration of 15 mg meloxicam 60 minutes prior to odontectomy was found more effective in reducing pain, facial edema and expressions of TNF-Î± after odontectomy of impacted mandibular third molar compared with placebo.